The effect of moving games on educators in schooling educational institutions - Yusupbaeva Amangul Saparbaevna; Saparbekova Aqdidar Isabek qizi (Genius Journals, 2021)
Educational games provide children with new knowledge and concepts. These games develop the child's all-round development, cognitive process, sensory culture, speech activity, mental abilities. Following the rules of the game enriches the content of the game. Natural objects are widely used in educational games. The child's agenda should include time and space for educational play
Keywords: School; education; institution; speech